Partial loss of VE-cadherin improves long-term outcome and cerebral blood flow after transient brain ischemia in mice. Issue 1 (December 2016) - Gertz, Karen; Kronenberg, Golo; Uhlemann, Ria; Prinz, Vincent; Marquina, Ruben; Corada, Monica; Dejana, Elisabetta; Endres, Matthias
Abstract Background VE-cadherin is the chief constituent of endothelial adherens junctions. However, the role of VE-cadherin in the pathogenesis of cerebrovascular diseases including brain ischemia has not yet been investigated. Methods VE-cadherin heterozygous (VEC+/- ) mice and wildtype controls were subjected to transient brain ischemia by 30 min filamentous middle cerebral artery occlusion (MCAo)/reperfusion. Results Acute lesion sizes as assessed by MR-imaging on day 3 did not differ between genotypes. Unexpectedly, however, partial loss of VE-cadherin resulted in long-term stroke protection measured histologically on day 28. Equally surprisingly, VEC+/- mice displayed no differences in post-stroke angiogenesis compared to littermate controls, but showed increased absolute regional cerebral blood flow in ischemic striatum at four weeks. The early induction of VE-cadherin mRNA transcription after stroke was reduced in VEC+/- mice. By contrast, N-cadherin and β-catenin mRNA expression showed a delayed, but sustained, upregulation up to 28 days after MCAo, which was increased in VEC+/- mice. Furthermore, partial loss of VE-cadherin resulted in a pattern of elevated ischemia-triggered mRNA transcription of pericyte-related molecules α-smooth muscle actin (α-SMA), aminopeptidase N (CD13), and platelet-derived growth factor receptor β (PDGFR-β). Conclusions Partial loss of VE-cadherin results in long term stroke protection. On the cellular and molecular level, this effect appears to be mediated by improved endothelial/pericyte interactions and the resultant increase in cerebral blood flow. Our study reinforces accumulating evidence that long-term stroke outcome depends critically on vascular mechanisms.